TINJAUAN YURIDIS TINDAK PIDANA PENGGELAPAN MOBIL YANG MENJADI JAMINAN LEASING PADA LEMBAGA PEMBIAYAAN DITINJAU DARI PASAL 372 DAN PASAL 64 Ayat 1 KUHP” (Studi Kasus Putusan No. 345/Pid.B/2014/PN.Dpk) - Surya Oktarina (Universitas Pamulang, 2016)
The number of cases of embezzlement of cars that occurred in the city of Depok by the buyer (lender) is detrimental for the leasing. Being thought of now is by increasing criminal acts of embezzlement of leasing cars as collateral. With the loss of the insurer by the actions of car buyers who commit fraud, another problem is the difficulty of law enforcement agencies in dealing with such cases. This is because the initial reporting by the injured party is a matter of civil law that they are due to violation of the treaty agreed, but with the embezzlement of objects that are still in power and the property of another person or institution that is based on the legal entity making the case bias, due to a shift in of civil law into criminal law offenses. In principle the sale of cars based on the agreement between the creditor and the pembiayaa by deed of sale where in this deed creditors have the right to goods in control, but the goods are still wholly owned by the guarantor.Keywords: Crime, Fraud, Security Leasing